Empirical Examination of the Poisson Regression Residuals for the Evaluation of Influential Points. (17th May 2022) - Khan, Aamna; Ullah, Muhammad Aman; Amin, Muhammad; Muse, Abdisalam Hassan; Aldallal, Ramy; Mohamed, Mohamed S.
Abstract : A common practice is to get reliable regression results in the generalized linear model which is the detection of influential cases. For the identification of influential cases, the present study focuses to compare empirically the performance of various existing residuals for the case of the Poisson regression model. Furthermore, we computed Cook's distance for the stated residuals. In order to show the effectiveness of proposed methodology, data have been generated by using simulation, and further applicability of methodology is shown with the help of real data that followed the Poisson regression. The comparative analysis of the residuals is carried out for the detection of influential cases.